2022
DOI: 10.3390/rs14163884
|View full text |Cite
|
Sign up to set email alerts
|

BDS/GPS Multi-Baseline Relative Positioning for Deformation Monitoring

Abstract: The single-baseline solution (SBS) model has been widely adopted by the existing global navigation satellite system (GNSS) deformation monitoring systems due to its theoretical simplicity and ease of implementation. However, the SBS model neglects the mathematical correlation between baselines, and the accuracy and reliability can be degraded for baselines with long length, large height difference or frequent satellite signal occlusion. When monitoring large-area ground settlement or long-spanned linear object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Wang et al [1] evaluated both a multi-baseline solution (MBS) model and a constrained-MBS (CMBS) model that had prior constraints of the spatial-correlated tropospheric delay in deformation monitoring. The reliability and validity of the MBS model was verified using the GPS/BDS data set from ground-based settlement deformation monitoring, with a baseline length of about 20 km and a height difference of about 200 m. They reported that the MBS model reduced the positioning standard deviation (STD) and root-mean-squared (RMS) errors by up to (47.4/51.3/66.2%) and (56.9/60.4/58.4%) in the north/east/up components compared with the single-baseline solution (SBS) model, respectively.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Wang et al [1] evaluated both a multi-baseline solution (MBS) model and a constrained-MBS (CMBS) model that had prior constraints of the spatial-correlated tropospheric delay in deformation monitoring. The reliability and validity of the MBS model was verified using the GPS/BDS data set from ground-based settlement deformation monitoring, with a baseline length of about 20 km and a height difference of about 200 m. They reported that the MBS model reduced the positioning standard deviation (STD) and root-mean-squared (RMS) errors by up to (47.4/51.3/66.2%) and (56.9/60.4/58.4%) in the north/east/up components compared with the single-baseline solution (SBS) model, respectively.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Until now, a total of 44 BDS satellites are in normal operation, containing 15 BDS-2 satellites (5 GEO satellites, 7 inclined geosynchronous orbit [IGSO] satellites and 3 mediumearth orbit [MEO] satellites) and 29 BDS-3 satellites (2 GEO satellites, 3 IGSO satellites and 24 MEO satellites). There has been abundant research based on BDS-2/3, such as deformation monitoring [13,14], atmospheric sounding [15,16] and precise point positioning-real-time kinematic (PPP-RTK) positioning [17],etc. However, the most aforementioned studies about BDS are based on ground-based observation data and LEO spaceborne GPS observation data, while less onboard BDS observation has been applied for real-time LEO POD.…”
Section: Introductionmentioning
confidence: 99%